Co widzisz? "Profesor" Johna Katzenbacha jako horror psychologiczny. Kilka uwag - Anna Gemra (Zagadnienia Rodzajów Literackich)
John Katzenbach’s novel — What comes next (2010) — does not seem to be a horror, because it tells a crime story: the kidnapping, imprisonment of a teenager, and the creation and sharing of an Internet series with the audience, the motive of which is the sophisticated abuse of the girl. However, the issues related to what is happening in the psyche of the characters and what their behavior says about their personality traits come to the fore. The narrator skillfully builds an ambience of horror, based on traditional comprehensions of normality and abnormality, health and illness; using an extremely closed and extremely (seemingly) open space, knowledge and non-knowledge, certainty and uncertainty, a state of a permanent (yet impossible to interpret unequivocally) threat. Following Charles Brockden Brown, Katzenbach relinquishes ‘classic’ monsters such as zombies or vampires in favor of a potential monster, which may be the human mind. This is the proper locus horridus: an area completely inaccessible to human recognition, in which the most terrifying fantasies and the beasts that grow from them can lurk. In the novel by Katzenbach the real monster is not therefore ‘some stranger’, but ‘our stranger’ — the one we carry inside, usually without noticing it.